2017
DOI: 10.1016/j.pmrj.2017.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Age‐Related Changes in Morphology and Function of Scapular Muscles in Asymptomatic People

Abstract: IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…5,17 We considered that the probe should be placed in the longitudinal axis of each muscle, based on previous reports. 27,28,39 Second, we did not examine several items that could affect muscle elasticity, such as ROM, humeral torsion, posterior inferior glenohumeral ligament and capsule, and ball velocity and location in this study. Although we examined all participants in approximately the same shoulder position, the actual tension of the muscle varies with the amount of humeral torsion, which could be a potential confounder because the association between muscle stiffness and rotational range can be affected by torsion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…5,17 We considered that the probe should be placed in the longitudinal axis of each muscle, based on previous reports. 27,28,39 Second, we did not examine several items that could affect muscle elasticity, such as ROM, humeral torsion, posterior inferior glenohumeral ligament and capsule, and ball velocity and location in this study. Although we examined all participants in approximately the same shoulder position, the actual tension of the muscle varies with the amount of humeral torsion, which could be a potential confounder because the association between muscle stiffness and rotational range can be affected by torsion.…”
Section: Discussionmentioning
confidence: 99%
“…For the lower trapezius, the lateral edge of the transducer was placed 5 cm below the root of the spine of the scapula, and the body of the transducer was inclined approximately 55 to the long axis of the lower trapezius. 27,28 For the serratus anterior, the transducer was placed on the midaxillary line at the level of the inferior angle of the scapula along the angle of the rib. 28 Previous reports have suggested that it is necessary to measure the muscle elasticity with the probe placed in the longitudinal axis of the muscle fibers in order to achieve accurate and reliable measurements in USWE.…”
Section: Ultrasound Assessments Of Posterior Shoulder Muscle Stiffnessmentioning
confidence: 99%
See 1 more Smart Citation
“…As a mean of comparison, data from 12 healthy participants (mean age 29.0 ± 5.2) was recorded during a single session, in identical conditions as for the patients. Mean age of the two groups significantly differed ( P < 0.0001), but considering the simplicity of the task and on the basis of a previous work stating no difference of scapular muscle activity and balance of activity between different age groups ( Morise et al, 2017 ), we considered that comparison was possible and appropriate.…”
Section: Methodsmentioning
confidence: 99%
“…The mechanism leading to an increased risk of developing a painful shoulder with advancing age is multifactorial and includes dysfunction of the scapular muscles and degeneration of the rotator cuff tendons. Morise et al (2017) investigated the electromyographic activity and muscle thickness of the trapezius, deltoid, and serratus anterior muscles in 45 asymptomatic subjects and found that the lower trapezius muscles were significantly thinner in the older adults than in the younger adults. A previous review by Keener et al (2019) pointed out that poor vascularity of the rotator crescent might contribute to degenerative rotator cuff tendon tears.…”
Section: Introductionmentioning
confidence: 99%